Impact analysis of the linkage between agricultural exports and agriculture’s share of Gross Domestic Product in South Africa : a case of Avocado, Apple, Mango and Orange from 1994 to 2011 - Bulagi, Mushoni Benedict (University of Limpopo (Turfloop Campus), 2014)
The role of agricultural exports to agriculture’s share of Gross Domestic Product (GDP) in South Africa is of extreme importance and exhibits strong interest from all parts of the economy. Many believe that agriculture can salvage the declining economic growth under such global economic conditions. The decision to diversify and expand exports of these avocados, apples, mangoes and oranges will improve the South African economy’s unstable conditions. This study accounts for all the factors that are truly unique to South African’s economy. Therefore, the study will help to shift the focus of avocado, apple, mango and orange growers to export more due to the international market demand for such produce. The aim of the study was to analyse the link between avocado, apple, mango and orange exports and agriculture’s share of Gross Domestic Product in South Africa. The specific objectives are to determine the correlation between avocado, apple, mango and orange exports and the agriculture’s share of Gross Domestic Product in South Africa, investigate the contribution of avocado, apple, mango and orange exports and the agriculture’s share of Gross Domestic Product in South Africa, determine the growth rate (trends) of avocado, apple, mango and orange exports and determine the volatility of avocado, apple, mango and orange exports. The study used secondary time series data that covered a sample size of 17 years (1994 - 2011) of avocado, apple, mango and orange exports in South Africa. Two Stages Least Square models and Growth rate and Volatility models were used for data analysis. i Empirical results for agricultural exports equation revealed that agricultural economic growth in South Africa was significant with a positive coefficient. While a negative relationship between the Net Factor Income (NFI) and the agricultural exports in South Africa was noticed. Real Capital Investments had a significant positive coefficient. Consequently, results from agricultural economic growth equation revealed that agricultural exports were significant with a positive correlation. A relationship between NFI and agricultural GDP was also witnessed. Like other variables, Real Capital Investment was significant but negatively correlated. The results of growth rate and volatility models showed positive trends. Furthermore, results showed that the quantity of agricultural exports was positively related to agricultural economic growth. Another point of interest was that while these exports were positive and significantly related, the magnitude of its coefficient is smaller than the coefficients of Real Capital Investments. It is in this framework that the positive correlation exists between agriculture economic growth and agricultural exports. It is recommended that investment opportunities in the agricultural sector need to be investigated further because there is limited knowledge of the subject. The Department of Agriculture, Forestry and Fishery and the private sector need to join hands and build a mutual relationship to aid develop an agricultural economy which can be able to exports more than what it imports. This can also be done by subsidising farmers with capital to relieve them of other expenses.
Thesis (MA. Agricultural Management (Agricultural Economics)) -- University of Limpopo, 2014
Keywords: Agricultural exports; Gross Domestic Product; 338.10968; Agriculture -- Economic aspects -- South Africa; Produce trade -- South Africa; Exports -- South Africa; Agricultural industries -- South Africa; Gross domestic product